RANCANGAN SISTEM DISKLESS UNTUK GAME CENTER MENGGUNAKAN APLIKASI CCBOOT - Agustinus Rio Trilaksono; Indra Hiswara (Institut Teknologi dan Bisnis Swadharma, 2021)
Since the launch of the game to be one of the sports fields, namely e-sports, a new business sector has grown to facilitate gamers to compete or practice together, namely the Game Center. Many e-sports players choose to practice and compete in game centers because the computer specifications provided are usually quite high and are supported by more stable internet speeds. Game Center XYZ is a game center whose client computer is active continuously for almost 24 hours, making the durability of existing computer devices decreasing, especially hard disk devices. A hard drive that is used continuously will result in a weakening of the hard drive's performance. So that the performance of the computer as a whole can be disrupted. Problems that often occur, for example, BSOD, existing data becomes corrupted, there are bad sectors on the hard disk that cause data to become unreadable. The purpose of this study is to produce a diskless network system that operates on a client-server basis. This research produces a diskless system with a star topology that connects 1 pc server and 5 client pc. The diskless system runs well and the client computer's performance is more optimal.